Utilization of Houseyards with Hydroponic Cultivation in Sampe Raya Village, Bahorok District with Nursery Student Activity, Himadita Nursery - Sebayang, Nur Ulina Warnisyah; Ichsana, Khairul; Nasution, Faris Naufal Adha (Talenta Publisher, 2023)
Many agricultural lands have switched to non-agricultural functions, especially in urban areas. For this reason, efforts are needed to be able to continue carrying out agricultural business activities on limited land, namely by utilizing yards through hydroponic cultivation. The purpose of this community service activity is to improve the ability of the community in Sampe Raya Village, Bahorok District in developing agriculture through simple vegetable hydroponics by utilizing the yard of the house so as to produce healthy vegetables. It can be identified the problems of partners in Sampe Raya Village, namely the lack of knowledge about simple vegetable cultivation techniques using the hydroponic system, the lack of training and outreach about hydroponics, and the lack of understanding about the use of home yards. The solution offered to partners is counseling and socialization of simple hydroponic techniques in Sampe Raya Village. The results of this activity were that the people who took part in the socialization activities had new knowledge and were able to utilize their own yards with hydroponic cultivation which can be made simply by using styrofoam.